Impact of Daily Lower‐Body Negative Pressure or Cycling Followed by Venous Constrictive Thigh Cuffs on Bedrest‐Induced Orthostatic Intolerance - Jan‐Niklas Hönemann; Fabian Hoffmann; Laura de Boni; Peter Gauger; Edwin Mulder; Stefan Möstl; Karsten Heusser; Marie‐Therese Schmitz; Marcel Halbach; Steven S. Laurie; Stuart M. C. Lee; Brandon R. Macias; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Orthostatic intolerance occurs following immobilization in patients on Earth and in astronauts after spaceflight. Head‐down tilt bedrest is a terrestrial model for weightlessness and induces orthostatic intolerance. We hypothesized that lower‐body negative pressure (LBNP) or cycling followed by wearing venous constrictive thigh cuffs mitigates orthostatic intolerance after head‐down tilt bedrest. Methods and Results We enrolled 47 healthy individuals (20 women, 35±9 years) to a 30‐day strict head‐down tilt bedrest study. During bedrest, they were assigned to 6 hours of 25 mm Hg LBNP (n=12) per day and 1 hour of supine cycling followed by 6 hours of venous constriction through thigh cuffs 6 days per week (n=12), 6 hours of daily upright sitting (positive control, n=11), or no countermeasure (negative control, n=12). We measured orthostatic tolerance as the time to presyncope during 80° head‐up tilt testing with incremental LBNP before and immediately after bedrest. We determined plasma volume with carbon monoxide rebreathing before and at the end of bedrest. After bedrest, orthostatic tolerance decreased 540±457 seconds in the control group, 539±68 seconds in the cycling group, 217±379 seconds in the LBNP group, and 289±89 seconds in the seated group (P<0.0001 time point, P=0.009 for group differences). Supine and upright heart rate increased in all groups following bedrest. Plasma volume was only maintained in the cycling group but decreased in all others (interaction countermeasure×time point P<0.0001). Conclusions Six hours of moderate LBNP training was as effective as sitting in attenuating orthostatic intolerance after 30 days of head‐down tilt bedrest. Daily cycling exercise followed by 6 hours of wearing venous constrictive thigh cuffs, while maintaining plasma volume, did not improve orthostatic tolerance. Registration URL: https://www.bfarm.de/EN; Identifiers: DRKS00027643 and DRKS00030848.